Vaccination Status of Hospitalized Patients with Covid-19 Infection during 4th Wave in Tertiary Care Hospital of Pakistan - Muhammad Saqib, Talha Mahmud, Rabbia Abbas, Muhammad Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The first COVID-19 vaccination was developed in December 2020. Effectiveness of different vaccines to prevent symptomatic COVID infection varies from 50% to 95% while effectiveness at preventing the critical disease and death ranges between 79 to 100%. Aim: To see vaccination status of hospitalized patients with COVID infection and to compare severity & mortality among vaccinated and non-vaccinated patients during 4th wave of COVID-19. Methods: This cross-sectional study was conducted in the Department of Pulmonology Shaikh Zayed Hospital, Lahore. The duration of study was 4 months from 01-07-2021 to 31-10-2021. Results: Total 121 patients having ages between 28 and 85 years; there were 77(63.6%) males & 44 (36.4%) females.Twenty four (20%) study participants were fully vaccinated, 14% were partially vaccinated and 66% of patients were not vaccinated. Most of the fully vaccinated patents had mild disease (58.3%), while, non-vaccinated patients either had severe disease (57.5%) or they were in critical condition (22.5%). All deaths in our study were recorded in non-vaccinated patients (28.8%). Conclusion: We concluded that patients who are fully vaccinated have less severe disease and low mortality rate as compared to non-vaccinated patients. Keywords: COVID-19, Vaccination